Implementation of Ethnoscience-based Guided Inquiry Learning on The Scientific Literacy and The Character of Elementary School Students - Alim, Alim; Sarwi, Sarwi; Subali, Bambang (Journal of Primary Education)
Building literacy education and students character in the 21st century began to be developed specifically in schools. The development of character education and the improvement of mastery literacy can be done by habituation and ethnoscience-based guided inquiry learning. The purpose of this study was to learn the implementation of ethnoscience-based guided inquiry learning on the literature and students character. The place of this research is at SDN 2 Wonosobo and SDN 5 Wonosobo, Wonosobo Regency. The type of research is a mixed method, with embedded experimental design. The sample in this study amounted to 56 students, for qualitative data samples, three samples were selected which obtained poor pretest (SP-1), moderate (SP-2), and high (SP-3) values. Data collection is done by test, observation, and documentation methods. The results of this study show a significant effect on the implementation of ethnoscience-based guided inquiry learning and the mastery of students literacy. This can be seen from the significance value of p (asymp. Sig. 2 tailed) of 0,000. The character development of students varied enough from SP-1, SP-2, and SP-3, and showed better development from each meeting. The conclusion in this study shows that ethnoscience-based guided inquiry learning gives a significant influence on the mastery of scientific literacy and the student's character.